RUMAH SEBAGAI PUSAT PENDIDIKAN & RUANG IBADAH - Poppy Alexandra Caroline (SAGACITY : Journal of Theology and Christian Education, 2021)
Home is the main place and the first environment for children to get education since they are born into the world. During this pandemic, people's conditions are getting worse. The house becomes the center of education, through which spiritual values are instilled so that children's behavior can develop and have an impact on everyone. With education carried out at home, the growth and development of children can be monitored properly. The house is also a place of worship in everyday life. A child will follow the behavior at home so that family members must be role models in instilling spiritual values. Education and worship in the family can shape the character and spirituality of children. Based on the explanation above, a question arises which is the formulation of the problem, namely: Why is the house a center of education and a place of worship? How can every Christian family play a role in the home to provide education to children and carry out worship with the family so that children can gain knowledge and spiritual growth? Through literature or literature research, it can provide understanding for all parents in building a house as an educational center and a place of worship.